Soil hydrophobicity in fynbos: measuring the impacts of woody invasive alien plant species and fire and ecological benefits - Fisher, Ruth-Mary Corne (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.